Prevalence and pattern of dyslipidemia in newly detected type 2 diabetes mellitus and its correlation with anthropometric parameters - Sukumar, Cynthia A.; Ramachandran, Arunachalam; K., Sudeep (International Journal of Research in Medical Sciences, 2021)
Background: Globally 425 million people have diabetes mellitus (DM) of which 90% are type 2 DM. India carries nearly 70 million cases of DM. India is called the diabetes capital of the world. The escalating epidemic of type 2 diabetes has been attributed to increasing obesity and longevity. Due to the additive cardiovascular risk of hyperglycemia and hyperlipidemia, lipid abnormalities should be aggressively detected and treated as a part of comprehensive diabetic care. The study aimed at detecting the occurrence and pattern of dyslipidemia in newly-detected type 2 diabetic patients in a tertiary care hospital in South India. Methods: This cross-sectional study was conducted over a period of eighteen months. It comprised of 50 newly detected diabetics above the age of 18 years who satisfied the inclusion and exclusion criteria. Results: Fifty patients were included in the study which included 18 males and 32 females. The body mass index (BMI) was abnormal in 62% (as per the Asian criteria) and in 42% (as per the WHO criteria). The waist circumference (WC) was found to be high in 82% and 70% as per the Asian and the WHO criteria, respectively. Forty six percent of the population was found to have elevated total cholesterol levels. LDL was increased in 70% of the study population while triglycerides were elevated in 40%, total cholesterol in 46% and low HDL in 76% of the patients. Conclusions: A significant correlation was found between the fasting blood sugars (FBSs) and serum triglycerides. There was a positive correlation noted between the dyslipidemia and the anthropometric parameters recorded.